2010
DOI: 10.1089/cap.2009.0047
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Placebo Response in Randomized Controlled Trials of Psychotropic Drugs for Children and Adolescents with Internalizing Disorders

Abstract: Predictors of placebo response in internalizing disorders of youths parallel those in adult studies, with the exception of race. These predictors should be considered when designing placebo-controlled trials in youths to enhance findings of true drug-placebo differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 39 publications
4
52
0
Order By: Relevance
“…Among the patient characteristics frequently accused of driving the placebo response are sex (with larger placebo responses in women) and (younger) age. Although these factors were shown to be relevant in some trials (Thijs et al, 1990;Freeman and Rickels, 1999;Rheims et al, 2008;Cohen et al, 2010;Yildiz et al, 2011;Agid et al, 2013;Arakawa et al, 2015), a recent review (Weimer et al, 2015a) of 75 systematic reviews and metaanalyses including more than 1500 trials, 150,000 patients, and 40 medical indications revealed that age and sex were not significant predictors of placebo responses in RCT, despite occasional evidence from experimental research (Aslaksen et al, 2007;Weimer et al, 2013b).…”
Section: B Influence Of Patient Characteristicsmentioning
confidence: 99%
“…Among the patient characteristics frequently accused of driving the placebo response are sex (with larger placebo responses in women) and (younger) age. Although these factors were shown to be relevant in some trials (Thijs et al, 1990;Freeman and Rickels, 1999;Rheims et al, 2008;Cohen et al, 2010;Yildiz et al, 2011;Agid et al, 2013;Arakawa et al, 2015), a recent review (Weimer et al, 2015a) of 75 systematic reviews and metaanalyses including more than 1500 trials, 150,000 patients, and 40 medical indications revealed that age and sex were not significant predictors of placebo responses in RCT, despite occasional evidence from experimental research (Aslaksen et al, 2007;Weimer et al, 2013b).…”
Section: B Influence Of Patient Characteristicsmentioning
confidence: 99%
“…Placebo response-the degree of symptomatic improvement in patients receiving placebo relative to those treated with the active medication-represents a particularly problematic issue in child and adolescent psychiatry. In this regard, some studies note placebo response rates of 40%-50% (Bridge et al 2009;Emslie et al 2014), although there is some suggestion that placebo response in pediatric patients may vary as a function of disorder (Cohen et al 2010). Increasing, but variable, placebo response rates in clinical trials involving youth with anxiety disorders may result in an efficacious treatment not being statistically superior to placebo.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing, but variable, placebo response rates in clinical trials involving youth with anxiety disorders may result in an efficacious treatment not being statistically superior to placebo. In fact, some contend that the placebo response rate is key to detecting drug versus placebo differences within a trial and, in terms of clinical practice, to better detect those children and adolescents who would truly benefit from medication (Cohen et al 2010). Consequently, high placebo response rates in pediatric patients may result in effective treatments being abandoned and may further limit the psychopharmacologic armamentarium for youth with anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, when placebo response rate was >30%, only 1 in 5 antidepressants showed significant separation. A review of controlled trials of psychotropic drugs for children and adolescents with internalizing disorders found that, as in adults, the magnitude of placebo response was the most powerful predictor of the outcome of a trial, rather than the response of the active treatment itself (Cohen, et al 2010). This makes sense, considering the wide variation in the percentage of responders to active compounds in most studies with children and adolescents with internalizing disorders: 36-71% (MDD), 21-65% (OCD), and 56-91% (AD) (Bridge et al 2007).…”
Section: Discussionmentioning
confidence: 99%